2014
DOI: 10.1525/mp.2014.32.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyphonic Context, Instrumentation, and Metrical Location on Syncopation in Music

Abstract: IN MUSIC, THE RHYTHMS OF DIFFERENT INSTRUMENTSare often syncopated against each other to create tension. Existing perceptual theories of syncopation cannot adequately model such kinds of syncopation since they assume monophony. This study investigates the effects of polyphonic context, instrumentation and metrical location on the salience of syncopations. Musicians and nonmusicians were asked to tap along to rhythmic patterns of a drum kit and rate their stability; in these patterns, syncopations occurred amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
0
36
1
Order By: Relevance
“…'strong' and 'weak' beats), which provides a prior context for perceiving the succession of musical events over time (e.g. 'Waltz' vs. 'March') [15][16][17][18]. However, music features events that challenge metrical expectations, e.g.…”
Section: Predictions and The Drive To Move To A Musical Groovementioning
confidence: 99%
“…'strong' and 'weak' beats), which provides a prior context for perceiving the succession of musical events over time (e.g. 'Waltz' vs. 'March') [15][16][17][18]. However, music features events that challenge metrical expectations, e.g.…”
Section: Predictions and The Drive To Move To A Musical Groovementioning
confidence: 99%
“…In the case of syncopation, we can obtain an estimate of both the precision and the prediction error. The syncopation in a given musical rhythm can be calculated directly from the musical score, demonstrated, for example, by Longuet‐Higgins and Lee's formulation or Witek and colleagues’ adjusted formulation . The precision (metrical uncertainty) can be behaviorally estimated by measuring participants’ sensorimotor synchronization to the beat using finger‐tapping paradigms or motion capture or by neurophysiological measures …”
Section: The Predictive Coding Of Rhythmic Incongruity Modelmentioning
confidence: 99%
“…The syncopation in a given musical rhythm can be calculated directly from the musical score, demonstrated, for example, by Longuet-Higgins and Lee's formulation or Witek and colleagues' adjusted formulation. 19 The precision (metrical uncertainty) can be behaviorally estimated by measuring participants' sensorimotor synchronization to the beat using finger-tapping paradigms 20,21 or motion capture 22,23 or by neurophysiological measures. 24,26 In the following, we show how PC in general and the PCRI model in particular can help to explain experimental observations concerning musical rhythm and meter.…”
Section: The Predictive Coding Of Rhythmic Incongruity Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In another empirical study, my co‐authors and I found that while monophonic syncopations were perceived to be the least stable (i.e. violating most expectations), syncopations in polyphonic contexts – syncopations accompanied by one or two more instruments which emphasise the beat – were also experienced as unstable, although less so (Witek, Clarke, Kringelbach and Vuust ). In other words, syncopations in polyphonic contexts still make the groove incomplete and still require our participation.…”
Section: Filling In the Gapsmentioning
confidence: 99%